Establishing Standard Performance Measures in Adult Traumatic Brain Injury Patients. Issue 1 (July 2015) - Corliss, Brian M.; Hooten, Kristopher G.; Gul, Sarah Shireen; Neal, Dan; Murad, Gregory J.A.; Rahman, Maryam
Abstract : BACKGROUND: The Agency for Healthcare Research and Quality patient safety indicators (PSIs) and Centers for Medicare and Medicaid Services hospital-acquired conditions (HACs) are publicly reported metrics that illustrate the overall quality of care provided at an institution. The national incidences of PSIs and HACs in traumatic brain injury (TBI) patients were estimated using the Nationwide Inpatient Sample database. OBJECTIVE: To establish baseline incidences of PSIs and HACs among surgical TBI patients treated at nonfederal hospitals in the United States, and to identify patient factors contributing to these adverse events. METHODS: The Nationwide Inpatient Sample database was queried for patients admitted with International Classification of Diseases, Ninth Revision diagnosis codes consistent with TBI between 2002 and 2011. The incidences of PSIs and HACs were estimated for TBI patients and evaluated for correlation with multiple factors, including comorbidity score, teaching hospital status, and insurance status. RESULTS: There were 15403 total PSIs among 24012 TBI patients. There were only 165 HACs among 24012 TBI patients. Only sepsis, deep vein thrombosis, and pressure ulcers occurred in more than 1% of patients. Patient age, sex, comorbidity score, and teaching hospital status were all found to significantly impact PSI incidence. Comorbidity score was found to significantly impact HAC incidence. Compared with private insurance, Medicaid patients developed significantly more HACs. CONCLUSION: These data may be used as reference values for hospitals reporting their own rates and seeking to improve the quality of care they provide for TBI patients. ABBREVIATIONS: AHRQ, Healthcare Research and Quality HAC, hospital-acquired condition ICP, intracranial pressure LOS, length of stay MS-DRG, Medicare Severity Diagnosis Related Group NIS, Nationwide Inpatient Sample PSI, patient safety indicator TBI, traumatic brain injury